(untitled) (Olhares, 2020)
In a cartography of the contemporary field-territory of the Brazilian playwriting, this article traces an overview of the published texts in the last decades, also emphasizing the strategies for this, from the call of publishers specialized in the area to the competitions; from public notices to collections made by public and private institutions or even made by the authors themselves, the main instruments for the realization of the playwriting produced in book.